Analisis Peran Mahasiswa dalam Mendukung Praktik Keberlanjutan Melalui Program Kampus Hijau di UIN Raden Intan Lampung - Putri, Neza Navilla; Yetri, Yetri; Wiliyanti, Vandan (Jurnal Ilmiah Global Education, 2025)
This study aims to determine the influence of the green campus program in the college environment, identify its long-term impact on students ' environmentally friendly behavior, and examine its contribution to the development of sustainability on campus and surrounding communities. Environmental and sustainability issues are a global concern that demands the active role of various institutions, including universities through green campus programs to instill sustainability values through environmentally friendly policies and behaviors in a responsible campus environment. In this study, the method used quantitative methods to analyze data researchers using Orange Data Mining software. The research sample consisted of 500 respondents from various study programs at the Faculty of tarbiyah and teacher training and environmental ambassador students, thus providing a comprehensive overview of the perception and behavior of students related to the green campus program. The results showed that students have a positive tendency in implementing a sustainable lifestyle, with an average score of 4.06 and a standard deviation of 0.9. The perception of the effectiveness of education and socialization of sustainability is also high, with an average score of 3.82 and a standard deviation of 1.0. The Data showed that student perceptions were relatively homogeneous and consistent. In line with that, the challenge remains in ensuring the internalization of sustainability values equally across all student groups. All data obtained showed that the perception of students is relatively homogeneous and consistent, indicated by the value of standard deviation that tends to be low. In line with that, the challenge remains in ensuring that all students not only understand the concept of sustainability, but also internalize it into real behavior equally. Differences in levels of awareness and practice can be influenced by internal factors such as motivation and knowledge, as well as external factors such as availability of facilities and institutional support. Therefore, it is recommended that educational institutions strengthen supporting infrastructure and expand environmental education and socialization strategies in a comprehensive and sustainable manner. This research contributes significantly to the development of strategies for high environmental progress and serves as a guide for other institutions in implementing effective green campus programs.